Recurrent diarrhea associated with enterotoxigenic Clostridium perfringens in 2 dogs. - Weese, J S (2001)
Two dogs were diagnosed with enterotoxigenic Clostridium perfringens-associated diarrhea. Diarrhea was responsive to antimicrobial therapy, but recurred after treatment was ceased. Clostridium perfringens enterotoxin was present in feces during diarrheic episodes but not when feces were normal. Both dogs responded to a prolonged course of oral cephalexin and dietary modification.